Integrated histopathology, spatial and single cell transcriptomics resolve cellular drivers of early and late alveolar damage in COVID-19 - Lee, Jimmy Tsz Hang; Barnett, Sam N.; Roberts, Kenny; Ashwin, Helen; Milross, Luke; Cho, Jae-Won; Huseynov, Alik; Woodhams, Benjamin; Aivazidis, Alexander; Li, Tong; Majo, Joaquim; Chaves, Patricia; et al. (Nature communications, 2025)
The most common cause of death due to COVID-19 remains respiratory failure. Yet, our understanding of the precise cellular and molecular changes underlying lung alveolar damage is limited. Here, we integrate single cell transcriptomic data of COVID-19 and donor lung tissue with spatial transcriptomic data stratifying histopathological stages of diffuse alveolar damage. We identify changes in cellular composition across progressive damage, including waves of molecularly distinct macrophages and depletion of epithelial and endothelial populations. Predicted markers of pathological states identify immunoregulatory signatures, including IFN-alpha and metallothionein signatures in early damage, and fibrosis-related collagens in late damage. Furthermore, we predict a fibrinolytic shutdown via endothelial upregulation of SERPINE1 /PAI-1. Cell-cell interaction analysis revealed macrophage-derived SPP1 /osteopontin signalling as a key regulator during early steps of alveolar damage. These results provide a comprehensive, spatially resolved atlas of alveolar damage progression in COVID-19, highlighting the cellular mechanisms underlying pro-inflammatory and pro-fibrotic pathways in severe disease. Here the authors characterise the cellular and molecular progression of lung alveolar damage in severe COVID-19 patients using integrated histopathology and cell atlassing, pinpointing a role for macrophage SPP1 signalling to vasculature in this process.